PENGARUH DIGITAL MARKETING DAN KERAGAMAN PRODUK TERHADAP MINAT BELI PADA PENGGUNA E-COMMERCE SHOPEE - Nisa', Nabilla Khoirun; Sudarwanto, Tri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022, 2022)
Today the development of technology and the internet has a great influence on the marketing sector. People are getting used to digital marketing carried out by sellers to market their products. The diversity of products sold with digital marketing makes people more interested so that there is interest in buying to online shop. The purpose of this study is to find out the impact of digital marketing and product diversity on buying interest in Shopee e-commerce application users study in the community of Margomulyo Village, Margomulyo District, Bojonegoro Regency. This type of research is quantitative descriptive with sampling using non probability sampling and sampling methods using accidental sampling techniques with a total of respondents 91 people who own and use the Shopee e-commerce application to shop. The data source uses primary data in the form of questionnaires with a likert scale. Data processing is carried out using IBM SPSS Statistics version 22 for windows application with multiple linear regression test analysis. The results of this study show that there is a positive and significant influence on digital marketing variables and product diversity on buying interest